Investment-related-trade measures (UN New YorkUS, 1999)
Examines several categories of investment-related trade measures (IRTMs) viz. market access restrictions, market access development preferences, export promotion devices and export restrictions. Looks at the categories in terms of their relative importance, frequency of use and impact on national and international trade and investment outcomes.
DC